Investigation of the Influence of Modes of Intensive Plastic Deformation on the Process of Grain Refinement of Titanium Alloy Ti-13Nb-13Zr at Equal-Channel Angular Pressing and Subsequent Rotary Forging Compression - Kengesbekov, A.B.; Serikbaikyzy, A.; Baizhan, D.; Batanov, Y.Y.; Kairbaeva, L.S. (Bulletin of the Karaganda University. “Physics” Series., 2025)
Ultrafine-grained materials are currently of great interest due to their excellent mechanical and functional properties. One of the most effective methods to obtain such materials with a unique combination of microstructure and properties is intense plastic deformation (IPD). This paper deals with the development of an efficient IPD method for Ti-13Nb-13Zr titanium alloy based on a combined approach involving equal channel angular pressing (ECAP) and subsequent rotational forging compression (“RFC”). Ti-13Nb-13Zr titanium alloy was pressed at different temperatures using an equal channel angular pressing (ECAP) process through a channel angle of 130° for several passes, followed by rotational forging compression (“RFC”). Microstructural analysis showed that the application of combined processing (RCUP + RFC) transformed the coarsegrained (CG) structure into an ultrafine-grained structure (UFGS). In addition, the results of mechanical tests indicate that the application of combined processing method significantly increases the hardness and modulus of elasticity of titanium alloy Ti-13Nb-13Zr. These changes in the complex of properties allow us to consider this alloy as a highly effective alternative to traditional metallic materials used in biomedical implantology
Қарқынды пластикалық деформация режимдерінің Ti-13Nb-13Zr титан қорытпасының дəнін тең арналы бұрыштық престеу жəне одан кейінгі айналмалы-соғу сығымдау кезінде ұнтақтау процесіне əсерін зерттеу
Исследование влияния режимов интенсивной пластической деформации на процесс измельчения зерна титанового сплава Ti-13Nb-13Zr при равноканальном угловом прессовании и последующем вращательно-ковочном сжатии
Keywords: Intense plastic deformation; ultrafine-grained structure; equal-channel angular pressing; rotary forging compression; titanium alloys